PELAKSANAAN PEMANFAATAN PERPUSTAKAAN DI SLB NEGERI MANGGIS GANTING BUKITTINGGI - Rizki - Febrianda (Universitas Negeri Padang, 2013)
This research background by library in SLB Negeri Manggis Ganting Bukittinggi that still need to be perfected, where not all library requirements are met. The purpose of this research is to look deeper into how the implementation of the use of the library in SLB Manggis Ganting Bukittinggi in organizing the library that can be the best. This research use descriptive method with qualitative approach. Techniques used in collecting data are observation, interview and documentary, while data sources are library employee, manager the school budget, the head of the institution (the principal). Results showed implementation in the library of SLB Negeri Manggis Ganting Bukittinggi still qualify are still not meet the standards. In accordance with the above results it is recommended that the existing schools to pay more attention to activities of the library, by giving budgets and policies that can support library services and further improve the quality of service, especially students have a high interest in reading.